Construction Quality Control Study of Double-Layer Continuous Paving for Large-Thickness Cement-Stabilized Base - LongTing Ding; Xuancang Wang; Mengyuan Zhang; Jiaqi Meng; Tao Hu (Advances in Civil Engineering)
In order to verify the interlayer bonding effect of double-layer continuous paving technology of the thick cement-stabilized base and solve the construction quality control problem of the double-layer continuous paving, based on the interlayer bonding mechanism and the evenness passing mechanism, the laboratory interlayer adhesion test, field test of evenness disturbance, and compaction test were conducted to verify the continuous paving interlayer bonding state. The effect of interval time on interlayer bonding state, evenness, and compactness was analyzed, and construction quality control measures were proposed. The test results show that the double-layer continuous paving process could significantly improve the interlayer bonding state, but there is still a gap from the ideal state (completely continuous). The pull-off strength of continuous paving specimens was 2.1 times that of the discontinuous paving specimens; the shear strength was 2.4 times that of discontinuous paving specimens. At different paving intervals, the longitudinal evenness of the upper and lower layers has little difference. The 140 kN axle load controls the transverse evenness disturbance within 3 mm, which met the requirements of the specification. Based on the evenness passing mechanism, the evenness control standard of double-layer continuous paving base was proposed. The compaction process of double-layer continuous paving base was proposed, and the feasibility was verified through the field test of compaction. The best interval time for double-layer continuous paving was also proposed; it is recommended that the best time for paving the upper layer is after the lower layer is laid for 6 hours (the final setting time of the cement). The construction quality control measures proposed in this study provide a theoretical basis for the construction of double-layer continuous paving technology with thick cement-stabilized base.